New Testament eschatology: historical and cultural background - Buchanan, George Wesley (Mellen Biblical Press, 1993)
Instead of opting for one of the standard explanations of eschatology, this study looks for the origin of the concept in antiquity, requiring an examination of the Hebrew Scripture, the New Testament, the Dead Sea Scrolls, rabbinic literature, the church fathers, and surrounding Greek literature and history. It involves a study of the legal, hermeneutical, cultural, historical, and political thought forms of ancient expectations. Beliefs and practices related to eschatology are examined from eighth-century Isaiah to the end of the Crusades in relationship to the promised land and the doctrine of redemption. Insights are employed to understand such New Testament problems as the Battle of Armageddon and the mystical number 666. It also uncovers the contemporary consequences of this dynamic doctrine.